Artifacts in Histopathology – A Review - N. Aravindha Babu1 , E.P. Sridevi Anjuga2 , K.M.K.Masthan3 , E.Rajesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Histopathological examination is considered to be the gold standard technique for making a definitivediagnosis of various human body lesions. The handling of tissue specimens consists of extensive proceduresfrom the stage of surgical removal to the microscopic parts stained and placed. Owing to defective procedures,defects are normal in the tissue parts. These defects are known as artefacts. In histopathology artefactsmay cause serious errors and misdiagnosis. The precision of the histopathological diagnosis is based onremoving or reducing the artifacts in histopathological section.This article discusses the common artefactsfound during slide analysis alongside the remedial steps that can be performed to distinguish between anartifacts and the constituent tissue.